Cortisol response to traumatic stress to predict PTSD symptom development – a systematic review and meta-analysis of experimental studies - Engel, Sinha; Laufer, Sebastian; Klusmann, Hannah; Schulze, Lars; Schumacher, Sarah; Knaevelsrud, Christine (European Journal of Psychotraumatology, 2023)
Background: Pre-and post-traumatic hypothalamic–pituitary–adrenal (HPA) axis markers have been studied to predict posttraumatic stress disorder (PTSD) risk, but its acute reactivity cannot be measured in real-life settings. Experimental paradigms can depict the cortisol response to stimuli that simulate traumatic events. Objective: To review experimental studies on the cortisol response to traumatic stimuli and the correlation between cortisol and PTSD symptoms. Method: Experimental, (un-)published studies in German or English from any year were eligible if they confronted non-traumatized humans with traumatic stimuli, assessed cortisol before, during or after stimulus presentation and subsequent PTSD symptoms. The literature was searched via PubMed, PubPsych, PsychINFO, PsycArticle, Web of Science, EMBASE, ProQuest and ClinicalTrials.gov up to 16th February 2021. Risk of bias was assessed with the Cortisol Assessment List. Multilevel-meta-analyses were conducted under the random effects model. The standardized mean change (dSMC) indicated the cortisol response. Coefficient r indicated the correlations between cortisol and PTSD symptoms. Results: 14 studies, investigating 1004 individuals, were included. A cortisol response was successfully induced between 21 and 40 min post-presentation onset (kobservations = 25, dSMC = 0.15 [.03; .26]). Cortisol was not associated with overall or cluster-level PTSD symptoms. On a symptom-level, higher pre-presentation onset cortisol was correlated with lower state tension (k = 8, r = −.18 [−.35; −.01]), higher state happiness (k = 8, r = −.34 [−.59; −.03], variable inverted) and lower state anger (k = 9, r = −.14 [−.26; −.01]). Higher post-presentation onset cortisol was correlated with higher state happiness (k = 16, r = −.20 [−.33; −.06]) and lower state sadness (k = 17, r = −.16 [−.25; −.05]), whereas cortisol response was positively correlated with state anxiety (k = 9, r = .16 [0.04; 0.27]). Conclusions: Experimental paradigms effectively induce a cortisol response. Higher basal cortisol, higher cortisol, as measured after traumatic stimulus presentation, and a lower cortisol response were associated with more adaptive emotional reactions. These markers did not predict longer-term PTSD symptom